Tradisi Literasi Dalam Bingkai Adab: Studi Perilaku Membaca Siswa di MI Nurul Hidayah - Nur Mahmudah; Fahmul Hikam Al Ghifari; Abd Haris (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims to explore how literacy traditions are formed, nurtured, and practiced within the framework of adab (Islamic manners) at MI Nurul Hidayah, Urangagung, Sidoarjo. Using a qualitative approach and case study method, data were gathered through observation, in-depth interviews, and documentation. The findings reveal that literacy practices at the school emphasize not only reading skills but also integrate Islamic moral values such as discipline, politeness, responsibility, and respect for knowledge and teachers. The support of teachers, the head of the madrasah, and parental involvement are key factors in cultivating a respectful and meaningful reading culture. This research underscores that cultivating literacy in Islamic elementary education can be a path to character building when framed with the values of adab.